Sexual and Reproductive Health and Reproductive Coercion in Women Victim/Survivors Receiving Housing Support - Grace, Karen Trister (Journal of family violence, 2023)
Housing instability and intimate partner violence (IPV) compromise women’s sexual and reproductive health (SRH) through reduced contraceptive access and increased risk of unintended pregnancy. This study describes the reproductive health status and needs of IPV survivors receiving housing support and explores factors influencing their experience of reproductive coercion (RC), specifically. Cross-sectional baseline data from a quasi-experimental study of 70 IPV survivors enrolled in housing programs in the Baltimore, MD, metropolitan area from June 2019 through December 2020 were analyzed. Of the 70 women enrolled in the study, 70.3 percent (n = 45) desired to avoid pregnancy, but 57.4 percent were either using no contraceptive method (31.2%) or methods with low effectiveness (26.2%). Approximately, 1 in 6 women (16.4%, n = 11) experienced RC in the past 3 months, which was associated with frequency and severity of IPV (p = 0.001 to 0.005) and PTSD (p = 0.001), as well as not sharing children with the abusive partner (p = 0.002). This study highlights reproductive health risks in an important and under-studied population of women seeking housing due to IPV. Leaving an abusive relationship is a uniquely vulnerable time, and also a time of opportunity, as women are accessing services that can be tailored to their SRH needs. Significant results highlight vulnerability to and consequences of RC in this population. This study has implications for IPV support programs and housing programs that serve women.